2021
DOI: 10.1093/nutrit/nuab007
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Dietary Patterns and Mental Health in Women: A Systematic Review

Abstract: Context Mental health may be influenced by some dietary patterns. Among common elements of beneficial patterns is high fruit and vegetable intake. However, no systematic review has been conducted to date, to our knowledge, that has assessed the influence of fruit and vegetable dietary patterns on a broad spectrum of mental health. Objective We conducted a systematic review, using the PRISMA guidelines, of the observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…The treatment protocol should not only include a broader dietary intervention, to ensure that an adequate amount of the vitamin D is obtained through the food sources, but should also include other dietary modifications. Such a modification should be based on the well-known association between diet and mental health, as indicated in the previous systematic reviews that determined the effects of fruit and vegetable intake [ 58 ] and various dietary patterns [ 59 ]. Moreover, physical activity should also be promoted as the confirmed factor associated with mental health [ 60 ], additionally supporting the positive influence of vitamin D.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment protocol should not only include a broader dietary intervention, to ensure that an adequate amount of the vitamin D is obtained through the food sources, but should also include other dietary modifications. Such a modification should be based on the well-known association between diet and mental health, as indicated in the previous systematic reviews that determined the effects of fruit and vegetable intake [ 58 ] and various dietary patterns [ 59 ]. Moreover, physical activity should also be promoted as the confirmed factor associated with mental health [ 60 ], additionally supporting the positive influence of vitamin D.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have shown inverse associations between fruit and vegetable intake and the risk of developing cardiovascular disease or cancer and total mortality [2][3][4]. Additionally, it has been suggested that there is a positive relationship between fruit and vegetable intake and mental health [5,6]. Therefore, strategies to increase fruit and vegetable intake should be developed to promote public health.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of fruit and vegetable intake may also help to address problems of overweight and obesity [ 12 , 13 ]. The potential benefits of higher fruit and vegetable consumption are diverse, including reduced incidence of headaches [ 14 ], maintenance of telomere length [ 15 ], and improved mental health [ 16 , 17 , 18 , 19 ]. Higher fruit and vegetable intake has also been associated with a range of other healthy lifestyle factors, including higher rates of exercise and not smoking [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%